Unravelling the Influence of Chlorogenic Acid on the Antioxidant Phytochemistry of Avocado (Persea americana Mill.) Fruit Peel - Gloria O. Izu; Emmanuel Mfotie Njoya; Gaetan T. Tabakam; Jennifer Nambooze; Kgalaletso P. Otukile; Seiso E. Tsoeu; Victoria O. Fasiku; Ayodeji M. Adegoke; Ochuko L. Erukainure; Samson S. Mashele; Tshepiso J. Makhafola; Mamello P. Sekhoacha; et al. (MDPI AG, 2024)
Oxidative stress is pivotal in the pathology of many diseases. This study investigated the antioxidant phytochemistry of avocado (Persea americana Mill.) peel. Different solvent extracts (dichloromethane, ethyl acetate, methanol, and water) of avocado peel were subjected to total phenol and flavonoid quantification, as well as in vitro radical scavenging and ferric reducing evaluation. The methanol extract was subjected to gradient column chromatographic fractionation. Fraction 8 (eluted with hexane:chloroform:methanol volume ratio of 3:6.5:0.5, respectively) was subjected to LC-MS analysis. It was assessed for cellular inhibition of lipid peroxidation and lipopolysaccharide (LPS)-induced ROS and NO production. The DPPH radical scavenging mechanism of chlorogenic acid was investigated using Density Functional Theory (DFT). The methanol extract and fraction 8 had the highest phenol content and radical scavenging activity. Chlorogenic acid (103.5 mg/mL) and 1-O-caffeoylquinic acid (102.3 mg/mL) were the most abundant phenolics in the fraction. Fraction 8 and chlorogenic acid dose-dependently inhibited in vitro (IC50 = 5.73 and 6.17 µg/mL) and cellular (IC50 = 15.9 and 9.34 µg/mL) FeSO4-induced lipid peroxidation, as well as LPS-induced ROS (IC50 = 39.6 and 28.2 µg/mL) and NO (IC50 = 63.5 and 107 µg/mL) production, while modulating antioxidant enzyme activity. The fraction and chlorogenic acid were not cytotoxic. DFT analysis suggest that an electron transfer, followed by proton transfer at carbons 3'OH and 4'OH positions may be the radical scavenging mechanism of chlorogenic acid. Considering this study is bioassay-guided, it is logical to conclude that chlorogenic acid strongly influences the antioxidant capacity of avocado fruit peel.